Phalacrotophora species (Diptera: Phoridae) with four subequal scutellar setae and notes on the other European species - Lengyel, Gábor Dániel (Zootaxa, 2009)
The unknown male of Phalacrotophora spectabilis Schmitz, 1925 and the unknown female of Phalacrotophora pictofasciata Schmitz, 1919 are described. New data on the Hungarian Phalacrotophora species are given. P. pictofasciata and P. spectabilis are new to the fauna of Hungary. A revised key with figures for the European species is presented.